PESANTREN SEBAGAI BASIS PENDIDIKAN KARAKTER ; TINJAUAN PSIKOLOGIS - Rela Mar'ati (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2014)
Character education is education that emphasizes the formation of character values in students. The goal of character edocation is: (1)to develop student sosially, ethically and academically by infusing character development into every aspect of the school culture and curriculum, (2) to help students develop good character which includes knowing, caring about and acting upon core ethical values such as : respect, responsibility, honest, fairness, compassion. Pesantren contributed greatly to the character of education in Indonesia, because the values prevailing in the pesantren-containing cargo formation of character. Those values are respect, brotherhood, sincerity and simplicity, independence, the prohibition violates the rules, and exemplary. As the basis of character education, values in pesantren is also a positive impact on mental health.